Preparation method of TA-Fe < 3 + > coated chlorella capable of improving biomass accumulation

By coating the bionic shell formed by the tanninic acid-iron (III) complex on the surface of Chlorella cells, the utilization rate and biomass accumulation of microalgae for bicarbonate are improved, and the carbon solidification of microalgae in the prior art is solved The problem of low efficiency has achieved efficient accumulation of biofuels.

CN119265177APending Publication Date: 2025-01-07LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411687397.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the utilization rate of bicarbonate by microalgae, which limits the carbon sequestration efficiency and biomass accumulation of microalgae biofuels.

Method used

By coating the tanninic acid-iron (III) complex on the surface of Chlorella cells, the utilization rate of bicarbonate and cell biomass accumulation were improved, and balls were performed using BG-11 medium and light incubator. Culture of algal cells, combined with the construction of TA-Fe3+ shell and mixed culture of NaHCO3 solution.

Benefits of technology

It significantly improves the biomass accumulation of Chlorella cells, enhances the utilization rate of exogenous bicarbonate, provides a new way of biofuel development, and is simple to operate and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265177A_ABST
    Figure CN119265177A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of cell surface engineering, and particularly relates to a preparation method of TA-Fe < 3 + > coated chlorella capable of improving biomass accumulation. According to the invention, chlorella cells are used as a coating object, a metal compound tannic acid-iron (III) (TA-Fe < 3 + >) is used as a coating material, and the shell has small influence on the physiological activity of the chlorella cells and has good biocompatibility. Compared with a natural chlorella cell, the surface of the chlorella cell is coated with a TA-Fe < 3 + > bionic shell, so that the viability and stability of the cell in a severe environment can be remarkably improved, the utilization rate of HCO3 <-> in the environment can be effectively improved through the synergistic effect between the shell and the cell, the biomass accumulation of the chlorella cell is further improved, and the biological activity of the chlorella cell is improved. And a new solution and possibility are provided for producing clean energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cell surface engineering, and specifically relates to a tannic acid-iron (III) (TA-Fe 3+ ) Preparation method of coated Chlorella. Background Art

[0002] Microalgae biomass has been widely studied as a raw material for biofuels. The increase in microalgae biomass is of great significance to the commercialization of microalgae biofuels. Among them, microalgae carbon fixation technology, as a bioenergy innovation in recent years, is characterized by its ability to achieve effective CO2 emission reductions and serve as a reliable source of renewable energy. Therefore, promoting the development of microalgae carbon fixation technology is not only an active exploration of the field of new energy development, but also a powerful contribution to the field of environmental governance. The pH value of natural water is generally between 6.5 and 8.5, and the carbonate compounds in the water are mainly HCO3 - In the form of HCO3 - The utilization rate of microalgae can increase the carbon fixation efficiency of microalgae. In the present invention, by coating the surface of Chlorella cells and increasing HCO3 - utilization rate and increase cell biomass.

[0003] Frank Caruso's research group proposed that the complex formed by natural polyphenols and iron (III) can quickly form a film on the surface of inorganic and organic templates, and has pH responsiveness and good cell compatibility [Science 2013, 341, 154]; Insung S. Choi's research group selected tannic acid and iron (III) complex as a protective layer on the surface of yeast cells, regulating the cell cycle through the formation and degradation of the cell shell [Angew. Chem. Int. Ed. 2014, 53, 12420]. Since algae cells play an important role in global warming and the fourth generation of biofuel production technology, the present invention selects natural polyphenol tannic acid (TA) and Fe 3+ As a bionic shell on the surface of Chlorella cells. Among them, the phenolic hydroxyl structure of tannic acid gives it unique physical and chemical properties. It has a strong adsorption capacity on different templates and can quickly combine with proteins, polysaccharides and other substances to change their physical and chemical behaviors. It can also combine with a variety of metal ions (such as Fe 3+ ) complexes and electrostatic interactions form complexes, and tannic acid has antioxidant properties and can capture free radicals. A layer of TA-Fe is coated on the surface of Chlorella cells through layer-by-layer self-assembly technology. 3+ The outer shell can not only increase the toughness of the cell surface and protect the Chlorella cells, but also increase the exogenous HCO3 - utilization rate and increase the biomass of Chlorella cells. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing coated Chlorella and its application in biomass accumulation. 3+ As a bionic shell, combined with TA-Fe 3+ The characteristics and protective effect of the bionic shell can improve the biomass accumulation performance of Chlorella cells.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A TA-Fe that can improve biomass accumulation 3+ The preparation method of coated chlorella comprises the following steps:

[0007] 1) Cultivation of Chlorella cells: Chlorella was selected as a coating template and cultured in a light incubator using BG-11 culture medium. When the number of Chlorella cells reached the logarithmic growth phase, the Chlorella cells were collected for coating experiments;

[0008] 2) washing the Chlorella cells in the logarithmic growth phase with sterile deionized water, collecting them by centrifugation, and finally dispersing the Chlorella cells to obtain a Chlorella cell suspension;

[0009] 3) Add 10-20 μL of TA aqueous solution to 0.9-1 mL of Chlorella cell suspension and mix for 10-20 min; then add 10-20 μL of FeCl3·6H2O aqueous solution and mix for 10-20 min, then add 0.5-1 mL of 3-(N-morpholino) propanesulfonic acid buffer and stabilize for 10-20 min to form a stable TA-Fe 3+ The shell layer was washed three times with deionized water to remove the residual TA and FeCl3, and the TA-Fe 3+ The coated Chlorella cells are TA-Fe 3+ @Chlorella.

[0010] Furthermore, in the above-mentioned preparation method, in step 1), the conditions for culturing in the light incubator are: temperature of 25° C., 12 hours of light and 12 hours of dark time per day, and light intensity of 2000 to 3000 LUX.

[0011] Further, in the above preparation method, in step 2), the OD of the obtained Chlorella cell suspension is 750 The value is 2.0~2.4.

[0012] Furthermore, in the above preparation method, in step 3), the concentration of the TA aqueous solution is 10 to 50 mg·mL -1 .

[0013] Furthermore, in the above preparation method, in step 3), the concentration of the FeCl3·6H2O aqueous solution is 4 to 20 mg·mL -1 .

[0014] Furthermore, in the above preparation method, in step 3), the pH of the 3-(N-morpholino)propanesulfonic acid buffer is 7-8, and the concentration is 15-25 mM.

[0015] TA-Fe prepared by any one of the preparation methods described above 3+ The method for culturing coated Chlorella is characterized by comprising the following steps: adding TAP culture medium to a sterilized culture bottle, and then adding TA-Fe 3+ The coated Chlorella was mixed and cultured with NaHCO3 solution.

[0016] Furthermore, in the above-mentioned culture method, the concentration of the NaHCO3 solution is 0 to 15 mg·mL -1 .

[0017] Furthermore, in the above-mentioned culture method, the pH range of the culture system is 6-9.

[0018] The beneficial effects of the present invention are:

[0019] 1. The present invention provides a TA-Fe 3+ The preparation method of coated Chlorella is simple to operate and highly efficient. 3+ The bionic shell constructed as the coating material has little effect on the activity of Chlorella cells and has high biocompatibility. This bionic shell can provide physical protection for the cells and protect the Chlorella cells from interference from adverse external factors.

[0020] 2. Taking bicarbonate as a representative of dissolved inorganic carbon, compared with natural algae cells, the cell combination constructed by the present invention effectively improves the utilization rate of bicarbonate. By measuring the dry weight yield of the combination of natural Chlorella cells and biomimetic shell cells, it is found that the biomass accumulation of the coated algae cells is significantly improved. Therefore, the synergistic effect between the constructed shell and Chlorella cells can promote the accumulation of biomass, and this technical method can provide a new way for the development of biofuels. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 for TA-Fe 3+ @Chlorella’s SEM image.

[0022] Figure 2 Natural chlorella and TA-Fe 3+@Chlorella and 5mg·mL -1 Biomass changes after co-cultivation with NaHCO3 solution.

[0023] Figure 3 Natural chlorella and TA-Fe 3+ @Chlorella and 10mg·mL -1 Biomass changes after co-cultivation with NaHCO3 solution.

[0024] Figure 4 Natural chlorella and TA-Fe 3+ @Chlorella and 15mg·mL -1 Biomass changes after co-cultivation with NaHCO3 solution.

[0025] Figure 5 Under the condition of pH 6, natural chlorella and TA-Fe 3+ @Chlorella and 5mg·mL -1 Biomass changes after co-cultivation with NaHCO3 solution.

[0026] Figure 6 Under the condition of pH 7, natural chlorella and TA-Fe 3+ @Chlorella and 5mg·mL -1 Biomass changes after co-cultivation with NaHCO3 solution.

[0027] Figure 7 Under the condition of pH 8, natural chlorella and TA-Fe 3+ @Chlorella and 5mg·mL -1 Biomass changes after co-cultivation with NaHCO3 solution.

[0028] Figure 8 Under the condition of pH 9, natural chlorella and TA-Fe 3+ @Chlorella and 5mg·mL -1 Biomass changes after co-cultivation with NaHCO3 solution. DETAILED DESCRIPTION

[0029] The present invention will be described in detail below with reference to the accompanying drawings and specific implementation schemes.

[0030] Example 1

[0031] (I)TA-Fe 3+ Preparation method of coated chlorella

[0032] Chlorella was selected as the coating template, and cultured in a light incubator using BG-11 medium (temperature was 25°C, light and dark time were 12 hours each day, and light intensity was 2000-3000LUX). When the number of Chlorella cells reached the logarithmic growth phase, the shell was modified, and the Chlorella cells in the logarithmic growth phase were collected. The Chlorella cells in the logarithmic growth phase were washed with sterile deionized water, collected by centrifugation (5000rpm), and finally the Chlorella cells were dispersed to obtain a Chlorella cell suspension (OD 750 value is 2.2). 10 μL of 20 mg mL -1 TA aqueous solution was added to 980 μL of Chlorella cell suspension and mixed for 10 min. Then 10 μL of 5 mg mL -1 The FeCl3·6H2O aqueous solution was mixed for 10 min, and then 1 mL of 3-(N-morpholino)propanesulfonic acid (MOPS, 15 mM) buffer was added to stabilize for 10 min to form a stable TA-Fe 3+ The shell layer was washed three times with deionized water to remove the residual TA and FeCl3, and the TA-Fe 3+ The coated Chlorella cells are TA-Fe 3+ @Chlorella.

[0033] (ii) TA-Fe 3+ Biomass monitoring experiment of encapsulated Chlorella

[0034] 3 mL TA-Fe 3+ @Chlorella was added to a 20 mL sterilized culture bottle, and 5 mL TAP medium and 2 mL NaHCO3 solution were added for mixed culture. 1 mL of cell suspension was taken from the culture bottle every 24 hours (shake well before sampling), centrifuged to remove the supernatant, and the sample was dried and weighed. Two groups of blank and coated controls were made to measure the change in dry weight. The concentration gradient of the NaHCO3 solution was 5 mg·mL -1 The culture conditions of the system are: 12 hours of light and 12 hours of darkness per day, pH of the culture system is 7, light intensity is 2000-3000LUX, and temperature is 25°C.

[0035] Example 2

[0036] (I)TA-Fe 3+ Preparation method of coated chlorella

[0037] Chlorella was selected as the coating template, and cultured in a light incubator using BG-11 medium (temperature was 25°C, light and dark time were 12 hours each day, and light intensity was 2000-3000LUX). When the number of Chlorella cells reached the logarithmic growth phase, the shell was modified, and the Chlorella cells in the logarithmic growth phase were collected. The Chlorella cells in the logarithmic growth phase were washed with sterile deionized water, collected by centrifugation (5000rpm), and finally the Chlorella cells were dispersed to obtain a Chlorella cell suspension (OD 750 value is 2.2). 10 μL of 20 mg mL -1 TA aqueous solution was added to 980 μL of Chlorella cell suspension and mixed for 10 min. Then 10 μL of 10 mg mL -1 The FeCl3·6H2O aqueous solution was mixed for 10 min, and then 1 mL of 3-(N-morpholino) propanesulfonic acid (MOPS, 20 mM) buffer was added to stabilize for 10 min to form a stable TA-Fe 3+ The shell layer was washed three times with deionized water to remove the residual TA and FeCl3, and the TA-Fe 3+ The coated Chlorella cells are TA-Fe 3+ @Chlorella.

[0038] (ii) TA-Fe 3+ Biomass monitoring experiment of encapsulated Chlorella

[0039] 3 mL TA-Fe 3+ @Chlorella was added to a 20 mL sterilized culture bottle, and 5 mL TAP medium and 2 mL NaHCO3 solution were added for mixed culture. Every 24 hours, 1 mL of cell suspension was taken from the culture bottle (shake well before sampling), centrifuged to remove the supernatant, and the sample was dried and weighed. Two groups of blank and coated controls were made to measure the change in dry weight. The concentration gradient of the NaHCO3 solution was 5 mg·mL -1 The culture conditions of the system are: 12 hours of light and 12 hours of darkness per day, pH of the culture system is 8, light intensity is 2000-3000LUX, and temperature is 25°C.

[0040] Example 3

[0041] (I)TA-Fe 3+ Preparation method of coated chlorella

[0042] Chlorella was selected as the coating template, and cultured in a light incubator using BG-11 medium (temperature was 25°C, light and dark time were 12 hours each day, and light intensity was 2000-3000LUX). When the number of Chlorella cells reached the logarithmic growth phase, the shell was modified, and the Chlorella cells in the logarithmic growth phase were collected. The Chlorella cells in the logarithmic growth phase were washed with sterile deionized water, collected by centrifugation (5000rpm), and finally the Chlorella cells were dispersed to obtain a Chlorella cell suspension (OD 750 value is 2.2). 10 μL of 20 mg mL -1 TA aqueous solution was added to 1 mL of Chlorella cell suspension and mixed for 10 min. Then 10 μL of 20 mg mL -1 The FeCl3·6H2O aqueous solution was mixed for 10 min, and then 1 mL of 3-(N-morpholino) propanesulfonic acid (MOPS, 20 mM) buffer was added to stabilize for 10 min to form a stable TA-Fe 3+ The shell layer was washed three times with deionized water to remove the residual TA and FeCl3, and the TA-Fe 3+ The coated Chlorella cells are TA-Fe 3+ @Chlorella.

[0043] (ii) TA-Fe 3+ Biomass monitoring experiment of encapsulated Chlorella

[0044] 3 mL TA-Fe 3+ @Chlorella was added to a 20 mL sterilized culture bottle, and 5 mL TAP medium and 2 mL NaHCO3 solution were added for mixed culture. Every 24 hours, 1 mL of cell suspension was taken from the culture bottle (shaken before sampling), centrifuged to remove the supernatant, and the sample was dried and weighed. Two groups of blank and coated controls were made to measure the change in dry weight. The concentration gradient of the NaHCO3 solution was 10 mg·mL -1 The culture conditions of the system are: the illumination time is 12 hours day and night, the pH of the culture system is 9, the illumination intensity is 2000-3000LUX, and the temperature is 25°C.

[0045] Tests were performed by scanning electron microscopy, such as Figure 1 As shown, TA-Fe 3+ The surface of the coated Chlorella cells is rough, which is due to the TA and Fe 3+ Complexation occurs to form a metal organic complex TA-Fe 3+ , it can be clearly observed that there are many particles on the cell surface, forming a dense shell layer, which increases the roughness of its surface.

[0046] In the biomass monitoring experiment, at different initial NaHCO3 concentrations, the dry weight of algal cells before and after coating increased with time. -1 When monitoring on the 7th day, the biomass accumulation of the coated algae cells was significantly increased compared with the natural algae cells, such as Figure 2 Then, the concentration of NaHCO3 was increased to 10 mg·mL -1 and 15 mg mL -1 (like Figure 3-4 ), the biomass accumulation of coated algal cells was higher than that of natural algal cells.

[0047] To investigate the effect of different pH (6-9) culture conditions on biomass accumulation (e.g. Figure 5-8 ), 5 mg·mL was added to the system -1 of NaHCO3, when the pH of the culture system was 8, the biomass accumulation of coated algal cells increased significantly.

Claims

1. A TA-Fe that can improve biomass accumulation 3+ The method for preparing coated chlorella is characterized in that: The steps include: 1) Cultivation of Chlorella cells: Chlorella was selected as a coating template and cultured in a light incubator using BG-11 culture medium. When the number of Chlorella cells reached the logarithmic growth phase, the Chlorella cells were collected for coating experiments; 2) washing the Chlorella cells in the logarithmic growth phase with sterile deionized water, collecting them by centrifugation, and finally dispersing the Chlorella cells to obtain a Chlorella cell suspension; 3) Add 10-20 μL of TA aqueous solution to 0.9-1 mL of Chlorella cell suspension and mix for 10-20 min; then add 10-20 μL of FeCl3·6H2O aqueous solution and mix for 10-20 min, then add 0.5-1 mL of 3-(N-morpholino) propanesulfonic acid buffer and stabilize for 10-20 min to form a stable TA-Fe 3+ The shell layer was washed three times with deionized water to remove the residual TA and FeCl3, and the TA-Fe 3+ The coated Chlorella cells are TA-Fe 3+ @Chlorella.

2. The preparation method according to claim 1, characterized in that: In step 1), the conditions for culturing in the light incubator are: temperature of 25° C., 12 hours of light and 12 hours of dark time per day, and light intensity of 2000 to 3000 LUX.

3. The preparation method according to claim 1, characterized in that: In step 2), the OD of the obtained Chlorella cell suspension is 750 The value is 2.0~2.

4.

4. The preparation method according to claim 1, characterized in that: In step 3), the concentration of the TA aqueous solution is 10 to 50 mg mL -1 .

5. The preparation method according to claim 1, characterized in that: In step 3), the concentration of the FeCl3·6H2O aqueous solution is 4 to 20 mg·mL -1 .

6. The preparation method according to claim 1, characterized in that: In step 3), the pH of the 3-(N-morpholino)propanesulfonic acid buffer is 7-8, and the concentration is 15-25 mM.

7. TA-Fe prepared by the preparation method according to any one of claims 1 to 6 3+ The method for culturing coated Chlorella is characterized by: The steps include: adding TAP medium to a sterilized culture bottle, followed by adding TA-Fe 3+ The coated Chlorella was mixed and cultured with NaHCO3 solution.

8. The culture method according to claim 7, characterized in that: The concentration of the NaHCO3 solution is 0 to 15 mg·mL -1 .

9. The culture method according to claim 7, characterized in that: The pH range of the culture system is 6-9.